Cheating by exploitation of developmental prestalk patterning in Dictyostelium discoideum. - Anupama Khare; Gad Shaulsky (PLoS Genetics, 2010)
The cooperative developmental system of the social amoeba Dictyostelium discoideum is susceptible to exploitation by cheaters-strains that make more than their fair share of spores in chimerae. Laboratory screens in Dictyostelium have shown that the genetic potential for facultative cheating is high, and field surveys have shown that cheaters are abundant in nature, but the cheating mechanisms are largely unknown. Here we describe cheater C (chtC), a strong facultative cheater mutant that cheats by affecting prestalk differentiation. The chtC gene is developmentally regulated and its mRNA becomes stalk-enriched at the end of development. chtC mutants are defective in maintaining the prestalk cell fate as some of their prestalk cells transdifferentiate into prespore cells, but that defect does not affect gross developmental morphology or sporulation efficiency. In chimerae between wild-type and chtC mutant cells, the wild-type cells preferentially give rise to prestalk cells, and the chtC mutants increase their representation in the spore mass. Mixing chtC mutants with other cell-type proportioning mutants revealed that the cheating is directly related to the prestalk-differentiation propensity of the victim. These findings illustrate that a cheater can victimize cooperative strains by exploiting an established developmental pathway.